Preliminary study on the application of digital guide plate in immediate autogenous tooth transplantation - DING Chengfang, Kadiliya·TUERXUNJIANG , Ailimaierdan·AINIWAER , Muladili·MAIHEMUTI , Dilihumaer·KUERBAN , WANG Ling (Editorial Office of Stomatology, 2024)
Objective To evaluate the preliminary application effects of digital guide plate in immediate autogenous tooth transplantation. Methods A total of 54 patients who attended the Department of Dental Surgery Clinic, the First Affiliated Hospital of Xinjiang Medical University for autotransplantation from October 2022 to October 2023 were collected, and randomly divided into the experimental group and the control group, with 27 cases in each group. In the control group, conventional autogenous tooth transplantation was carried out. In the experimental group, digital guide technology was added, and the operation time (including the time of extraction of the affected tooth and the donor tooth, the time of alveolar socket preparation, and the time of donor tooth in vitro), the healing of transplanted roots, and the clinical efficacy of transplanted teeth were recorded in the two groups, respectively. Results The average total surgical time, alveolar socket preparation time and the time of donor tooth in vitro of the test group were (23.77±4.32), (6.54±1.77) and (2.80±0.57) min, respectively, which were significantly less than those of the control group (P<0.05); the cervical distance deviation, apical distance deviation, depth deviation and angular deviation of the test group were smaller than those of the control group, and the difference was statistically significant (P<0.05); there was no statistical difference in root healing and clinical efficacy between the two groups (P>0.05); the number of trial implantation of 3D model teeth in the test group was significantly less than that in the control group (P<0.05). Conclusion The digital guide plate can effectively reduce the time for immediate autogenous tooth transplantation, accurately prepare the socket in the recipient area and successfully implant the donor tooth in a single pass, reducing the distance between the actual position and the preoperative design.